PENGARUH SIKAP, PENDIDIKAN DAN FAKTOR INFORMASI TERHADAP PERILAKU BERHENTI MEROKOK PADA PENDERITA HIPERTENSI DENGAN THEORY OF PLLANED BEHJAVIOR - Sefti Wulandari Sefti Wulandari; Wiwit Dwi Nurbadiah; Riza Fikriana (Program Studi S1 Ilmu Keperawatan dan Ners IKBIS Surabaya, 2023)
ABSTRAK BACKGROUND: Hypertension is a cardiovascular disease characterized by an increase in blood pressure, if not treated properly it will cause complications. The level of stress is a factor that triggers the recurrence of hypertension. So that stress management or stress management can prevent and minimize the recurrence of hypertension. The purpose of this study was to analyze stress management in patients with hypertension in Tegalsari Village, Kepanjen District. METHOD:The design of this study used observational analytic with a cross sectional approach. The sample used is 92 people with Purposive Sampling Technique. The data collection process used a questionnaire sheet, then data processing was carried out. Statistical test using Linear Regression using the help of a windows 10 laptop with SPSS 22.0.RESULT:The results of the linear regression test showed that the attitude variable about hypertension had a p-value <0.544. While the education variable is 67.6%. Meanwhile, the information factor variable in hypertension sufferers with a p-value <0.190 and the variable value of intention to stop smoking in hypertension patients with a p-value <0.142.CONCLUSION:Based on these results, the variable that affects the patient is the education variable in patients with hypertension.